(untitled) (Materiali di Estetica. Terza serie, 2019)
The essay aims to highlight the links between Dorfles’ Le oscillazioni del gusto (The Oscillations of Taste) (1958 and 1970) and David Hume’s classic essay Of the Standard of Taste (1757). Taste becomes the core of aesthetic experience, making the relationship between subjectivity and shared values problematic, but necessary. Like Hume, Dorfles also conceives taste, despite its variety and variability, as a process of cultural exercising that finds its operative grammar in the balance between facility and novelty and in the dimension of delicacy.